Future behavioural of console gamers and mobile gamers : Are they differ? - Syahrulanuar, Ngah; Rahi, Samar; Long, Fei; Gabarre, Cécile; Rashid, Aamir; Abdul Hafaz, Ngah (Springer Science and Business Media B.V., 2024)
Since the pandemic, a greater flexibility to work and study from home led to increased opportunities for online gaming. This resulted in the resilience of the online game industry in times of weakened individual purchasing power caused by the economic downturn. Following a new trend in customer behaviour to invest in better game play experience and performance, revenue from the online game industry reached new heights, particularly revenue from the purchase of viqueryrtual items. Therefore, it is crucial to investigate the repurchase intention of gamers towards virtual items. This article reports on the comparison of the effect of aesthetic design towards overall perceived value and gamers’ satisfaction among console and mobile gamers using the Stimulus-Organism-Response Model. In addition, findings highlight the relationship between the overall perceived value and user satisfaction toward the repurchase intention of virtual items among online gamers. A cross-sectional study involving a snowball sampling method was conducted to collect data online from 498 respondents. Results from Partial Least Squares Structural Equation Modelling (PLS-SEM) supported all hypotheses for direct effects. For the MGA analysis, all hypotheses were supported except for the relationship between perceived value and repurchase intention which showed no significance difference between console gamers on mobile gamers. All other hypotheses show that console gamers have a strong effect compared to mobile gamers. Therefore, the study contributes to online gamers’ behavioural literature, while providing online game developers with meaningful information on appropriate strategies to support the repurchase intention of virtual items.